Negative electrode active material, secondary battery, and electronic device
By using a granular negative electrode active material composed of a first particle with a high spherical shape and a low spherical shape and a second particle with a large particle size, the gram capacity and cyclic performance problems of hard carbon materials in lithium-ion batteries are solved, and higher energy density and cyclic stability are achieved.
Patent Information
- Application Number
- CN202411930177.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
As the negative electrode material of lithium-ion batteries, existing hard carbon materials have problems such as low gram capacity, low first-time Coulomb efficiency, high charge and discharge potential, and the single-morphological hard carbon materials have low compaction density and poor electrode bonding, which affect the capacity and cycling performance of the battery cell.
A granular negative electrode active material including the first particle and the second particle is used. The spherical degree of the first particle is greater than the second particle, and the particle size Dv50 of the first particle is smaller than the second particle. By regulating the spherical degree and particle size of the particles, good contact and adhesion performance between the particles is ensured.
The compaction density of the battery electrode sheet is improved, the transmission efficiency of lithium ions between the negative electrode active materials is enhanced, and the energy density and circulation performance of the secondary battery are improved.
Smart Images

Figure CN119725469A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode active material, a secondary battery and an electronic device. Background Art
[0002] The negative electrode active material plays the role of a carrier of lithium ions and electrons during the charge and discharge process of the battery, accounting for 5%-15% of the battery cost and is one of the four main materials in the battery system. With the development of society, the demand for secondary batteries with high energy density, long cycle life and low self-discharge rate is becoming increasingly significant. Graphite is the most commonly used negative electrode material for lithium-ion batteries, and its capacity development has reached its limit. Therefore, it is urgent to develop a high-capacity negative electrode material to meet the growing performance requirements.
[0003] Among the many negative electrode active materials to be developed, hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion, and fast charge and discharge. However, hard carbon materials still face problems such as low gram capacity, low first coulomb efficiency, and high charge and discharge potential. Hard carbon materials with a single morphology also face problems such as low compaction density and poor electrode bonding, which affect the capacity and cycle performance of the battery cell. Summary of the invention
[0004] The purpose of this application is to provide a negative electrode active material, a secondary battery and an electronic device to improve the energy density of the secondary battery. The specific technical solution is as follows:
[0005] According to the first aspect of the present application, the present application provides a negative electrode active material, which is in a granular form and includes a first particle and a second particle. The sphericity of the first particle is greater than the sphericity of the second particle, the sphericity of the first particle is 0.6 to 1.0, and the particle size Dv50 of the first particle is smaller than the particle size Dv50 of the second particle.
[0006] The negative electrode active material provided in the present application is granular and includes a first particle and a second particle. The negative electrode active material with the above characteristics avoids the problem of poor bonding performance caused by point contact between negative electrode active materials when there is only the first particle. At the same time, in the negative electrode active material provided in the present application, the first particles are evenly distributed between the second particles, and the first particles with higher sphericity and smaller particle size can slide during the cold pressing process of the pole piece, relieve the cold pressing stress, avoid hard contact between particles, and thus avoid stress concentration. It effectively solves the problem of cold pressing and crushing of larger particles, avoids exposing more new surfaces of the negative electrode material after cold pressing, further avoids electrolyte loss, and improves the energy density and cycle performance of the battery cell. In addition, the compaction density of the negative electrode pole piece containing the above negative electrode active material is also improved, and the negative electrode adhesive can better wrap the first particle, and the cross section of the first particle has a larger contact area with the irregular surface of the second particle, which can effectively promote the transmission of lithium ions between the negative electrode active materials. At the same time, by regulating the sphericity and particle size of the first particles and the second particles in the negative electrode active material, the first particles and the second particles can be better combined, so that the particles in the negative electrode active material can have good contact. The negative electrode active material of the present application is applied to secondary batteries, which can increase the compaction density of the battery electrode, thereby achieving the goal of increasing the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0007] In some embodiments of the present application, the sphericity of the first particles is 0.7 to 1.0.
[0008] In some embodiments of the present application, the sphericity of the second particles is 0.1 to 0.6; or, the sphericity of the second particles is 0.2 to 0.6.
[0009] In some embodiments of the present application, the ratio of the sphericity of the first particle to the second particle ranges from 1.1 to 10.0; or, the ratio of the sphericity of the first particle to the second particle ranges from 1.1 to 5.5.
[0010] By regulating the sphericity parameters of the first and second particles in the negative electrode active material within the above range, the negative electrode active material particles can slide during the cold pressing process of the pole piece, relieve the cold pressing stress, avoid hard contact between particles, thereby avoiding stress concentration, avoiding the exposure of more new surfaces of the negative electrode material and further electrolyte loss after cold pressing, and further good contact between the negative electrode particles, which can effectively promote the transmission of lithium ions between the negative electrode active materials. If the sphericity parameter of the first particle exceeds the above range, such as, below the above range, it will cause stress concentration between the first particle and the second particle, cold pressing will easily cause particle crushing, and the first efficiency and energy density will be reduced. If it is higher than the above range, it will cause the contact surface between the first particle and the second particle to be reduced, the adhesive bonding effect is poor, and the particles fall off during the cycle, and the cycle retention rate is reduced. Applying the negative electrode active material with the above characteristics to a secondary battery can further increase the compaction density of the battery pole piece, thereby further achieving the improvement of the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0011] In some embodiments of the present application, the particle size Dv50 of the first particles is in the range of 1 μm≤Dv50≤10 μm; or, the particle size Dv50 of the first particles is in the range of 3 μm≤Dv50≤8 μm.
[0012] In some embodiments of the present application, the particle size range of the second particles is 1.5 μm ≤ Dv50 ≤ 20 μm; or, the particle size Dv50 range of the first particles is 8 μm ≤ Dv50 ≤ 20 μm.
[0013] In some embodiments of the present application, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle is in the range of 0.05 to 0.9; or, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle is in the range of 0.1 to 0.9.
[0014] In some embodiments of the present application, by regulating the particle size of the first particle and the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the particle size parameter of the first particle exceeds the above range, for example, below the above range, it will lead to poor bonding effect of the adhesive, poor contact between small particles, and reduced lithium ion transmission efficiency. Above the above range, it will lead to decreased particle strength, cold pressing will easily lead to particle crushing, exposing new active surfaces, and the battery's first efficiency and cycle performance will decrease. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the goal of increasing the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0015] In some embodiments of the present application, the first particles include a hard carbon material.
[0016] In some embodiments of the present application, the second particles include a hard carbon material.
[0017] In some embodiments of the present application, the first particles and the second particles further contain a first element and a second element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; and the second element is N.
[0018] By regulating the first and second particles of the negative electrode active material to contain the first element and the second element, the first element can induce the storage of active metal ions in the negative electrode active material, further improving the storage capacity of active metal ions; the second element helps to expand the carbon layer spacing of the negative electrode active material, promotes the deintercalation of active metal ions in the active material, and can make the negative electrode active material have a high reversible capacity.
[0019] In some embodiments of the present application, based on the total mass of the negative electrode active material, the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1%.
[0020] In some embodiments of the present application, based on the total mass of the first particle, the content of the first element in the first particle is A1, based on the total mass of the second particle, the content of the first element in the second particle is A2, and A2 / A1 satisfies the following relationship: 0.8≤A2 / A1≤1.2; and / or, the content A1 of the first element in the first particle is in the range of 0.01% to 0.9%; and / or, the content A2 of the first element in the second particle is in the range of 0.01%-0.9%.
[0021] In some embodiments of the present application, based on the total mass of the negative electrode active material, the content of the second element relative to the total mass of the negative electrode active material is 0.01% to 3%.
[0022] In some embodiments of the present application, based on the total mass of the first particle, the content of the second element in the first particle is B1, the content of the second element in the second particle is B2, and B2 / B1 satisfies the following relationship: 0.8≤B2 / B1≤1.2; and / or, the content B1 of the second element in the first particle is in the range of 0.06% to 2.8%; and / or, the content B2 of the second element in the second particle is in the range of 0.05% to 3%.
[0023] In some embodiments of the present application, by regulating the first element content in the first particle and the second particle in the negative electrode active material within the above range, it is possible to further induce the storage of active metal ions in the negative electrode active material, further improve the storage capacity of active metal ions, and apply the negative electrode active material of the present application to a secondary battery, which can increase the gram capacity of the negative electrode of the battery, thereby improving the energy density of the secondary battery. In some embodiments of the present application, by regulating the N element content in the first particle and the second particle in the active material within the above range, it is helpful to further expand the carbon layer spacing of the negative electrode active material, further promote the deintercalation of active metal ions in the active material, and further make the negative electrode active material have a high reversible capacity.
[0024] In some embodiments of the present application, the ratio of the closed pore volumes of the first particles to the second particles is 0.75 to 1.0.
[0025] In some embodiments of the present application, the closed pore volume of the first particles is in the range of 0.05 to 0.4 cc / g; or, the closed pore volume of the first particles is in the range of 0.12 to 0.36 cc / g.
[0026] In some embodiments of the present application, the closed pore volume of the second particles is in the range of 0.06 to 0.4 cc / g; or, the closed pore volume of the second particles is in the range of 0.06 to 0.34 cc / g.
[0027] In some embodiments of the present application, by regulating the closed pore volume of the first particle and the second particle in the negative electrode active material within the above range, the active metal ion storage capacity can be increased, and at the same time, the active material has a lower energy storage platform, thereby increasing the active metal ion storage capacity. By regulating the closed pore volume ratio of the first particle and the second particle in the active material within the above range, the capacity difference between the particles can be avoided, and the active metal ions can be prevented from precipitating in the form of atoms when fully charged.
[0028] In some embodiments of the present application, the surfaces of the first particle and the second particle respectively have a carbon coating layer; the thickness of the carbon coating layer is 20 to 200 nm.
[0029] In some embodiments of the present application, the particle mass ratio of the first particles to the second particles is 0.6 to 3.0.
[0030] In some embodiments of the present application, the ratio of the ID / IG value of the first particle to the ID / IG value of the second particle is in the range of 0.93 to 1.12; and / or, the ID / IG value of the first particle is in the range of 1.0 to 1.3; and / or, the ID / IG value of the second particle is in the range of 1.0 to 1.3.
[0031] In some embodiments of the present application, the strength of the first particle and the second particle is tested using a nanoindentation method, and the particle strength ratio of the first particle to the second particle ranges from 1.1 to 2.8; or, the strength range of the first particle is 0.1 to 6 GPa; or, the strength range of the second particle is 0.1 to 6 GPa.
[0032] In some embodiments of the present application, in the negative electrode active material provided in the present application, a carbon coating layer is provided on the surface of the first particle and the second particle, and by controlling the thickness of the carbon coating layer within the above range, it helps to reduce defects on the surface of the particles, while reducing the exposure of the particle pore structure, thereby improving the first coulombic efficiency of the negative electrode active material, and making the negative electrode active material have a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0033] In some embodiments of the present application, by regulating the particle mass ratio of the first particles and the second particles in the negative electrode active material within the above-mentioned range, good contact between the negative electrode active material particles can be achieved. Applying the negative electrode active material of the present application to secondary batteries can increase the compaction density of the battery electrode sheets, thereby increasing the energy density of the secondary battery and improving the cycle performance of the secondary battery.
[0034] In some embodiments of the present application, I D is the peak area of D peak in the Raman spectrum of the material, I G is the peak area of the G peak in the Raman spectrum of the material. By controlling the ID / IG value of the first particle and the ID / IG value of the second particle of the negative electrode active material provided in the present application within the above range, it is shown that the provided negative electrode active material has a suitable defect degree, which can promote ion adsorption and binding, while reducing the irreversible capacity loss caused by a high defect degree, thereby helping to improve the gram capacity of the negative electrode active material.
[0035] In some embodiments of the present application, by regulating the particle strength ratio of the first particles and the second particles in the negative electrode active material provided by the present application within the above-mentioned range, it can be ensured that the particle morphology of the negative electrode plate is maintained during the cold pressing process, thereby improving the first coulombic efficiency of the negative electrode active material and improving the cycle performance of the secondary battery.
[0036] According to the second aspect of the present application, the present application further provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising the negative electrode active material described in any one of the first aspects of the present application. The negative electrode plate provided in the second aspect of the present application has a high capacity, and applying it to a secondary battery can increase the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0037] In some embodiments of the present application, the compaction density of the negative electrode active material layer is in the range of 0.90 to 1.3 g / cc; or, the compaction density of the negative electrode active material layer is in the range of 0.9 to 1.25 g / cc.
[0038] In some embodiments of the present application, the negative electrode sheet is used as the working electrode, and lithium metal is used as the counter electrode to assemble a half-cell, and a charge-discharge test is performed in the range of 0 to 2.5 V vs Li+ / Li. Based on the charge-discharge curve obtained by the charge-discharge test, in the range of 0 to 0.20 V (vs Li + / Li) is recorded as C10 mAh / g, the gram capacity at 0 to 0.20V (vsLi+ / Li) is recorded as C11 mAh / g; the gram capacity at 0.2 to 2.5V (vs Li+ / Li) is recorded as C12 mAh / g, and the negative electrode active material satisfies 600≤C10≤850, 300≤C11≤590; and / or, 0.4≤C12 / C11≤1.2.
[0039] In some embodiments of the present application, the compaction density of the negative electrode active material layer is in the range of 0.90 to 1.3 g / cc; preferably, the compaction density of the negative electrode active material layer is in the range of 0.95 to 1.20 g / cc. By adjusting the compaction density of the negative electrode active material layer within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0040] In some embodiments of the present application, the negative electrode is used as the working electrode and lithium metal is used as the counter electrode to assemble a half-cell. + / Li range, and the charge and discharge curves obtained based on the charge and discharge test are between 0 and 0.20V (vs Li + / Li) is recorded as C10 mAh / g, and the total gram capacity is recorded as C10 mAh / g at 0 to 0.20 V (vs Li + / Li) is recorded as C11 mAh / g; at 0.2 to 2.5V (vs Li + / Li) is recorded as C12 mAh / g, and the negative electrode active material satisfies 600≤C10≤850, 300≤C11≤590; and / or, 0.4≤C12 / C11≤1.2. By regulating C10, C11, and C12 corresponding to the negative electrode active material within the above range, the negative electrode active material layer can have a high total lithium storage gram capacity and a low average lithium desorption potential. The negative electrode active material layer having the above characteristics is used as the negative electrode of a lithium ion battery, which is conducive to further improving the energy density of the lithium ion battery.
[0041] According to the third aspect of the present application, the present application provides a secondary battery, which includes a positive electrode sheet, an electrolyte, and a negative electrode sheet provided by any embodiment of the second aspect of the present application. The secondary battery including the negative electrode sheet has high energy density and good cycle performance.
[0042] According to a fourth aspect of the present application, the present application provides an electronic device, which includes the secondary battery provided by any one embodiment of the third aspect of the present application. The electronic device including the secondary battery has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0044] Figure 1 The scanning electron microscope photographs of the negative electrode active materials prepared in Examples 1-5; wherein "1" represents the first particle, i.e., corresponding to Figure 1 The middle particle size is smaller and the sphericity is higher, and "2" indicates the second particle, which corresponds to the particle size with larger sphericity;
[0045] Figure 2 The negative electrode active material of Comparative Example 1 is Li / Li at 0V to 2.5V. + The charge and discharge curves within the potential range;
[0046] Figure 3 The negative electrode active material of Examples 1-5 is Li / Li at 0V to 2.5V. + The charge and discharge curves within the potential range;
[0047] Figure 4 The negative electrode active material of Example 2-4 is Li / Li at 0V to 2.5V + Charge and discharge curves within the potential range. DETAILED DESCRIPTION
[0048] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0049] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0050] Among the many negative electrode active materials to be developed, hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion, and fast charge and discharge. However, hard carbon materials still face problems such as low gram capacity, low first coulomb efficiency, and high charge and discharge potential. Hard carbon materials with a single morphology also face problems such as low compaction density and poor electrode bonding, which affect the capacity and cycle performance of the battery cell.
[0051] Based on this, the inventors of the present application started from the negative electrode active material itself and found through extensive research that by preparing negative electrode active materials with high gram capacity and controlling the particle morphology of the negative electrode active materials, the problems of poor adhesion and poor conductivity of the negative electrode plates can be solved, thereby increasing the compaction density of the battery plates, further increasing the energy density of the secondary battery and improving the cycle performance of the secondary battery.
[0052] According to the first aspect of the present application, the present application provides a negative electrode active material, the negative electrode active material is in a granular form, and the negative electrode active material includes a first particle and a second particle, the sphericity of the first particle is greater than the sphericity of the second particle, the sphericity of the first particle is 0.6 to 1.0, and the particle size Dv50 of the first particle is smaller than the particle size Dv50 of the second particle. Wherein, the particle size Dv50 of the first particle refers to the particle size that reaches 50% of the volume accumulation from the small particle size in the volume-based particle size distribution of the first particle; the particle size Dv50 of the second particle refers to the particle size that reaches 50% of the volume accumulation from the small particle size in the volume-based particle size distribution of the second particle.
[0053] The negative electrode active material provided in the present application is granular and includes a first particle and a second particle. The negative electrode active material with the above characteristics avoids the problem of poor bonding performance caused by point contact between negative electrode active materials when there is only the first particle. At the same time, in the negative electrode active material provided in the present application, the first particles are evenly distributed between the second particles, and the first particles with higher sphericity and smaller particle size can slide during the cold pressing process of the pole piece, relieve the cold pressing stress, avoid hard contact between particles, and thus avoid stress concentration. It effectively solves the problem of cold pressing and crushing of larger particles, avoids exposing more new surfaces of the negative electrode material after cold pressing, further avoids electrolyte loss, and improves the energy density and cycle performance of the battery cell. In addition, the compaction density of the negative electrode pole piece containing the above negative electrode active material is also improved, and the negative electrode adhesive can better wrap the first particle, and the cross section of the first particle has a larger contact area with the irregular surface of the second particle, which can effectively promote the transmission of lithium ions between the negative electrode active materials. At the same time, by regulating the sphericity and particle size of the first particles and the second particles in the negative electrode active material, the first particles and the second particles are better combined, which can make the particles in the negative electrode active material have good contact. The negative electrode active material of the present application is applied to secondary batteries, which can increase the compaction density of the battery electrode, thereby achieving the purpose of increasing the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0054] In some embodiments of the present application, the sphericity of the first particles is 0.7 to 1.0.
[0055] In some embodiments of the present application, the sphericity of the second particles is 0.1 to 0.6; or, the sphericity of the second particles is 0.2 to 0.6.
[0056] In some embodiments of the present application, the ratio of the sphericity of the first particle to the second particle ranges from 1.1 to 10.0; or, the ratio of the sphericity of the first particle to the second particle ranges from 1.1 to 5.5.
[0057] In some embodiments of the present application, in the negative electrode active material provided, the sphericity of the first particle is 0.6 to 1.0. Specifically, the sphericity of the first particle can be 0.6, 0.61, 0.62, 0.63, 0.64, 0.65, 0.66, 0.67, 0.68, 0.69, 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0 or a range consisting of any two of the above values. Preferably, the sphericity of the first particle can be 0.7 to 1.0. By regulating the sphericity parameter of the first particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the sphericity parameter of the first particle exceeds the above range, such as lower than the above range, it will cause stress concentration between the first particle and the second particle, and cold pressing will easily lead to particle crushing, and the first efficiency and energy density will be reduced. If it is higher than the above range, the contact surface between the first particle and the second particle will be reduced, the adhesive bonding effect will be poor, and the particles will fall off during the cycle, and the cycle retention rate will be reduced. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the improvement of the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0058] In some embodiments of the present application, in the provided negative electrode active material, the sphericity of the second particles is 0.1 to 0.6. Specifically, the sphericity of the second particles can be 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.6 or a range consisting of any two of the above values. Preferably, the sphericity of the second particles can be 0.2 to 0.6. By regulating the sphericity parameter of the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the sphericity parameter of the second particle exceeds the above range, for example, below the above range, the particle will have obvious sharp points, and electrons and lithium ions will easily enter the negative electrode, resulting in lithium precipitation, and it will be easy to pierce the diaphragm, resulting in battery failure. If it is higher than the above range, the contact surface between the first particle and the second particle will be reduced, the adhesive bonding effect will be poor, and the particles will fall off during the cycle, and the cycle retention rate will be reduced. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the improvement of the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0059] In some embodiments of the present application, in the negative electrode active material provided, the ratio of the sphericity of the first particle to the second particle ranges from 1.1 to 10.0. Specifically, the ratio of the sphericity of the first particle to the second particle can be: 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0, 11.1, 12.2, 13.4, 14.6, 15.8, 16.9, 17.0, 18.1, 19.2, 20.3, 21.4, 22.5, 23.6, 24.7, 25.8, 26.9, 27.0, 28.1, 29.3, 30.4, 31.5, 32.4, 33.5, 34.6, 35.7, 36.8, 37.9, 38.0, 39.1, 40.2, 41.4, 42.6, 43.7, 44.7, 45.8, 46.9, 50.1, 51.2, 52.6, 53.7, 54.7, 55.8 By regulating the sphericity ratio parameter of the first particle and the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the sphericity ratio parameter of the first particle and the second particle exceeds the above range, for example, if it is lower than the above range, the stress between the first particle and the second particle is concentrated, and the cold pressing is easy to cause the particles to be crushed, and the first efficiency and energy density are reduced. If it is higher than the above range, it will lead to poor adhesion and contact between particles, and lithium ion diffusion will be hindered. Applying the negative electrode active material with the above characteristics to secondary batteries can further improve the compaction density of the battery pole piece, thereby further improving the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0060] In some embodiments of the present application, the particle size Dv50 of the first particles ranges from 1 μm ≤ Dv50 ≤ 10 μm; or, the particle size Dv50 of the first particles ranges from 3 μm ≤ Dv50 ≤ 8 μm.
[0061] In some embodiments of the present application, the size range of the particle size Dv50 of the second particles is 1.5 μm≤Dv50≤20 μm; or, the size range of the particle size Dv50 of the first particles is 8 μm≤Dv50≤20 μm.
[0062] In some embodiments of the present application, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle is in the range of 0.05 to 0.9; or, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle is in the range of 0.1 to 0.9.
[0063] In some embodiments of the present application, in the negative electrode active material provided, the particle size Dv50 of the first particle is in the range of 1 μm ≤ Dv50 ≤ 10 μm, wherein the particle size Dv50 of the first particle refers to the particle size at which the volume accumulation reaches 50% from the small particle size in the volume-based particle size distribution of the first particle. Specifically, the particle size Dv50 of the first particle can be 1 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 8.6 μm, 8.7 μm, 8.8 μm, 8.9 μm, 9.0 μm, 9.5 μm, 10.0 μm or a range consisting of any two of the above values. Preferably, the particle size Dv50 of the first particle can be in the range of 3μm≤Dv50≤8μm. In some embodiments of the present application, by regulating the particle size Dv50 of the first particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the particle size parameter of the first particle exceeds the above range, such as below the above range, it will lead to poor bonding effect of the adhesive, poor contact between small particles, and reduced lithium ion transmission efficiency. Above the above range, it will lead to decreased particle strength, and cold pressing will easily cause particle crushing, exposing new active surfaces, and the battery's first efficiency and cycle performance will decrease. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the goal of increasing the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0064] In some embodiments of the present application, in the negative electrode active material provided, the second particle size Dv50 ranges from 1.5 μm ≤ Dv50 ≤ 20 μm, wherein the particle size Dv50 of the second particle refers to the particle size at which the volume accumulation reaches 50% in the volume-based particle size distribution of the second particle, measured from the small particle size. Specifically, the particle size Dv50 of the second particle can be 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, 10.5 μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm, 14.0μm, 14.5μm, 15.0μm, 15.5μm, 16.0μm, 16.5μm, 17.0μm, 17.5μm, 18.0μm, 18.5μm, 19.5μm, 20μm or a range consisting of any two of the above values. Preferably, the particle size Dv50 of the first particles ranges from 8μm≤Dv50≤20μm. In some embodiments of the present application, by regulating the particle size Dv50 of the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the particle size parameter of the second particle exceeds the above range, such as below the above range, it will lead to poor bonding effect of the adhesive, poor contact between small particles, and reduced lithium ion transmission efficiency. Above the above range, it will lead to decreased particle strength, cold pressing will easily lead to particle crushing, exposing new active surfaces, and the battery's first efficiency and cycle performance will decrease. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the improvement of the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0065] In some embodiments of the present application, in the negative electrode active material provided, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle is in the range of 0.05 to 0.9. Specifically, the ratio of the particle size Dv50 of the first particle to the particle size Dv50 of the second particle can be: 0.005, 0.01, 0.02, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.50, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58, 0.59, 0.60, 0.61, 0.62, 0.63, 0.64, 0.65 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range consisting of any two of the above values. Preferably, the ratio of the particle size Dv50 of the first particles to the particle size Dv50 of the second particles can be in the range of 0.1 to 0.9. In some embodiments of the present application, by regulating the ratio of the particle size Dv50 of the first particle and the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have further good contact. If the ratio of the particle size Dv50 of the first particle and the second particle exceeds the above range, such as below the above range, it will lead to poor bonding effect of the adhesive, poor contact between small particles, and reduced lithium ion transmission efficiency. Above the above range, the tip of the second particle will easily lead to stress concentration on the cross section of the first particle, and cold pressing will easily lead to particle crushing, exposing new active surfaces, and the first efficiency and cycle performance of the battery will decrease. Applying the negative electrode active material with the above characteristics to secondary batteries can further increase the compaction density of the battery pole piece, thereby further achieving the goal of increasing the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0066] In some embodiments of the present application, the first particles include a hard carbon material.
[0067] In some embodiments of the present application, the second particles include a hard carbon material.
[0068] In some embodiments of the present application, the first particle and the second particle further contain a first element and a second element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; the second element is N. The first element can induce the storage of active metal ions in the negative electrode active material, further improving the storage capacity of active metal ions; the second element helps to expand the carbon layer spacing of the negative electrode active material, promotes the deintercalation of active metal ions in the active material, and can make the negative electrode active material have a high reversible capacity.
[0069] In some embodiments of the present application, based on the total mass of the negative electrode active material, the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1%.
[0070] In some embodiments of the present application, based on the total mass of the first particle, the content of the first element in the first particle is A1, based on the total mass of the second particle, the content of the first element in the second particle is A2, and A2 / A1 satisfies the following relationship: 0.8≤A2 / A1≤1.2; and / or, the content A1 of the first element in the first particle is in the range of 0.01% to 0.9%; and / or, the content A2 of the first element in the second particle is in the range of 0.01%-0.9%.
[0071] In some embodiments of the present application, based on the total mass of the negative electrode active material, the content of the second element relative to the total mass of the negative electrode active material is 0.01% to 3%.
[0072] In some embodiments of the present application, based on the total mass of the first particle, the content of the second element in the first particle is B1, the content of the second element in the second particle is B2, and B2 / B1 satisfies the following relationship: 0.8≤B2 / B1≤1.2; and / or, the content B1 of the second element in the first particle is in the range of 0.06% to 2.8%; and / or, the content B2 of the second element in the second particle is in the range of 0.05% to 3%.
[0073] In some embodiments of the present application, in the negative electrode active material provided, based on the total mass of the negative electrode active material, the content of the first element relative to the total mass of the negative electrode active material is in the range of 0.01% to 1%. Specifically, the content of the first element relative to the total mass of the negative electrode active material can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the content of the first element in the negative electrode active material within the above-mentioned range, it is possible to further induce the storage of active metal ions in the negative electrode active material, further improving the storage capacity of active metal ions, and applying the negative electrode active material of the present application to secondary batteries, which can increase the gram capacity of the battery negative electrode, and thus can improve the energy density of the secondary battery.
[0074] In some embodiments of the present application, in the negative electrode active material provided, based on the total mass of the first particle, the content of the first element in the first particle is A1, based on the total mass of the second particle, the content of the first element in the second particle is A2, and A2 / A1 satisfies the following relationship: 0.8≤A2 / A1≤1.2. Specifically, the ratio of the content A2 of the first element in the second particle to the content A1 of the first element in the first particle A2 / A1 can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.1, 1.2 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the ratio A2 / A1 of the content A2 of the first element in the negative electrode active material in the second particle to the content A1 of the first element in the first particle within the above range, the difference between particles can be reduced, so that lithium ions are evenly stored in the entire negative electrode active material, thereby improving the cycle stability of the secondary battery.
[0075] In some embodiments of the present application, in the negative electrode active material provided, the content A1 of the first element in the first particle ranges from 0.01% to 0.9%. Specifically, the content A1 of the first element in the first particle can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the content A1 of the first element in the first particle in the negative electrode active material within the above range, it is possible to induce the storage of active metal ions in the negative electrode active material, further improve the storage capacity of active metal ions, and apply the negative electrode active material of the present application to a secondary battery, which can increase the gram capacity of the negative electrode of the battery, and thus can improve the energy density of the secondary battery.
[0076] In some embodiments of the present application, in the negative electrode active material provided, the content A2 of the first element in the second particle is in the range of 0.01%-0.9%. Specifically, the content A2 of the first element in the second particle can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the content A2 of the first element in the negative electrode active material in the second particle within the above range, the active metal ions can be induced to be stored in the negative electrode active material, further improving the storage capacity of the active metal ions, and applying the negative electrode active material of the present application to a secondary battery can increase the gram capacity of the negative electrode of the battery, thereby increasing the energy density of the secondary battery.
[0077] In some embodiments of the present application, in the negative electrode active material provided, based on the total mass of the negative electrode active material, the content of the second element relative to the total mass of the negative electrode active material is 0.01% to 3%. Specifically, based on the total mass of the negative electrode active material, the content of the second element relative to the total mass of the negative electrode active material can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.70%, 0.80%, 0.90%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62 60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the N element content in the negative electrode active material within the above range, it is helpful to further expand the carbon layer spacing of the negative electrode active material, further promote the deintercalation of active metal ions in the active material, and further make the negative electrode active material have a high reversible capacity.
[0078] In some embodiments of the present application, in the negative electrode active material provided, based on the total mass of the first particle, the content of the second element in the first particle is B1, the content of the second element in the second particle is B2, and the B2 / B1 satisfies the following relationship: 0.8≤B2 / B1≤1.2. Specifically, the ratio B2 / B1 of the content B2 of the second element in the second particle to the content B1 of the second element in the first particle can be 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.1, 1.2 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the ratio B2 / B1 of the content B2 of the second element in the second particle of the negative electrode active material to the content B1 of the second element in the first particle within the above range, the difference between particles can be reduced, so that lithium ions are evenly stored in the entire negative electrode active material, thereby improving the cycle stability of the secondary battery.
[0079] In some embodiments of the present application, in the negative electrode active material provided, the content B1 of the second element in the first particle is in the range of 0.06% to 2.8%. Specifically, the content B1 of the second element in the first particle can be 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the content B1 of the second element in the first particle in the negative electrode active material within the above-mentioned range, it can be achieved to help expand the carbon layer spacing of the negative electrode active material, promote the deintercalation of active metal ions in the active material, and enable the negative electrode active material to have a high reversible capacity while avoiding the increase in irreversible capacity caused by excessively high B1.
[0080] In some embodiments of the present application, in the negative electrode active material provided, the content B2 of the second element in the second particle is in the range of 0.05% to 3%. Specifically, the content B2 of the second element in the second particle can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0% or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the content B2 of the second element in the second particle in the negative electrode active material within the above-mentioned range, it can be achieved to help expand the carbon layer spacing of the negative electrode active material, promote the deintercalation of active metal ions in the active material, and enable the negative electrode active material to have a high reversible capacity while avoiding the increase in irreversible capacity caused by excessively high B1.
[0081] In some embodiments of the present application, the ratio of the closed pore volumes of the first particles to the second particles is 0.75 to 1.0.
[0082] In some embodiments of the present application, the closed pore volume of the first particles is in the range of 0.05 to 0.4 cc / g; or, the closed pore volume of the first particles is in the range of 0.12 to 0.36 cc / g.
[0083] In some embodiments of the present application, the closed pore volume of the second particles is in the range of 0.06 to 0.4 cc / g; or, the closed pore volume of the second particles is in the range of 0.06 to 0.34 cc / g.
[0084] In some embodiments of the present application, in the negative electrode active material provided, the ratio of the closed pore volume of the first particle to the second particle is in the range of 0.75 to 1.0. Specifically, the ratio of the closed pore volume of the first particle to the second particle can be 0.75, 0.76, 0.77, 0.78, 0.79, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0 or a range consisting of any two of the above values. In some embodiments of the present application, the ratio of the closed pore volume of the first particle to the second particle is regulated within the above range, which can improve the storage capacity of the active metal ions, while making the active material have a lower energy storage platform, thereby improving the energy density of the battery. By regulating the ratio of the closed pore volumes of the first particles and the second particles in the active material within the above range, capacity differences between the particles can be avoided and the precipitation of active metal ions in the form of atoms when fully charged can be avoided.
[0085] In some embodiments of the present application, in the negative electrode active material provided, the closed pore volume of the first particle ranges from 0.05 to 0.4 cc / g. Specifically, the closed pore volume of the first particle can be 0.05 cc / g, 0.06 cc / g, 0.07 cc / g, 0.08 cc / g, 0.09 cc / g, 0.1 cc / g, 0.11 cc / g, 0.12 cc / g, 0.13 cc / g, 0.14 cc / g, 0.15 cc / g, 0.16 cc / g, 0.17 cc / g, 0.18 cc / g, 0.19 cc / g, 0.20 cc / g, 0.21 cc / g, 0.22 cc / g, 0.23 cc / g, 0.24 cc / g. / g, 0.25cc / g, 0.26cc / g, 0.27cc / g, 0.28cc / g, 0.29cc / g, 0.30cc / g, 0.31cc / g, 0.32cc / g, 0.33cc / g, 0.34cc / g, 0.35cc / g, 0.36cc / g, 0.37cc / g, 0.38cc / g, 0.39cc / g, 0.4cc / g or a range consisting of any two of the above values. Preferably, the closed pore volume range of the first particle can be 0.12 to 0.36cc / g. In some embodiments of the present application, the closed pore volume of the first particle is regulated within the above range, which can increase the storage capacity of the active metal ions and make the active material have a lower energy storage platform, thereby increasing the energy density of the battery; at the same time, it avoids the generation of invalid closed pores, and also ensures that the particles have a certain strength, so as to avoid the particles from being crushed and broken during the cold pressing process, resulting in a decrease in capacity.
[0086] In some embodiments of the present application, in the negative electrode active material provided, the closed pore volume of the second particle is in the range of 0.06 to 0.4 cc / g. Specifically, the closed pore volume of the second particle can be 0.06 cc / g, 0.07 cc / g, 0.08 cc / g, 0.09 cc / g, 0.1 cc / g, 0.11 cc / g, 0.12 cc / g, 0.13 cc / g, 0.14 cc / g, 0.15 cc / g, 0.16 cc / g, 0.17 cc / g, 0.18 cc / g, 0.19 cc / g, 0.20 cc / g, 0.21 cc / g, 0.22 cc / g, 0.2 3cc / g, 0.24cc / g, 0.25cc / g, 0.26cc / g, 0.27cc / g, 0.28cc / g, 0.29cc / g, 0.30cc / g, 0.31cc / g, 0.32cc / g, 0.33cc / g, 0.34cc / g, 0.35cc / g, 0.36cc / g, 0.37cc / g, 0.38cc / g, 0.39cc / g, 0.4cc / g or a range consisting of any two of the above values. Preferably, the closed pore volume of the second particle can be 0.06 to 0.34cc / g. In some embodiments of the present application, the closed pore volume of the second particle is regulated within the above range, which can increase the storage capacity of the active metal ions and make the active material have a lower energy storage platform, thereby increasing the energy density of the battery; at the same time, it avoids the generation of invalid closed pores, and also ensures that the particles have a certain strength, so as to avoid the particles from being crushed and broken during the cold pressing process, resulting in a decrease in capacity.
[0087] In some embodiments of the present application, the surfaces of the first particle and the second particle respectively have a carbon coating layer; the thickness of the carbon coating layer is 20 to 200 nm.
[0088] In some embodiments of the present application, the particle mass ratio of the first particles to the second particles is 0.6 to 3.0.
[0089] In some embodiments of the present application, the ratio of the ID / IG value of the first particle to the ID / IG value of the second particle is in the range of 0.93 to 1.12; and / or, the ID / IG value of the first particle is in the range of 1.0 to 1.3; and / or, the ID / IG value of the second particle is in the range of 1.0 to 1.3.
[0090] (17) The strength of the first particle and the second particle is tested by a nanoindentation method, and the ratio of the strength of the first particle to the second particle is in the range of 1.1 to 2.8; or, the strength of the first particle is in the range of 0.1 to 6 GPa; or, the strength of the second particle is in the range of 0.1 to 6 GPa.
[0091] In some embodiments of the present application, in the provided negative electrode active material, the surfaces of the first particles and the second particles further have a carbon coating layer respectively; the thickness of the carbon coating layer is 20 to 200 nm. Specifically, the thickness of the carbon coating layer can be 20nm, 21nm, 22nm, 23nm, 24nm, 25nm, 26nm, 27nm, 28nm, 29nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm, 100nm, 105nm, 110nm, 115nm, 120nm, 125nm, 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm, 180nm, 185nm, 190nm, 195nm, 200nm or a range consisting of any two of the above values. In some embodiments of the present application, in the negative electrode active material provided in the present application, a carbon coating layer is provided on the surface of the first particle and the second particle, and by controlling the thickness of the carbon coating layer within the above range, it helps to reduce defects on the surface of the particles, while reducing the exposure of the particle pore structure, thereby improving the first coulombic efficiency of the negative electrode active material, and making the negative electrode active material have a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0092] In some embodiments of the present application, in the negative electrode active material provided, the particle mass ratio of the first particle to the second particle is 0.6 to 3.0. Specifically, the particle mass ratio of the first particle to the second particle can be 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the particle mass ratio of the first particle and the second particle in the negative electrode active material within the above range, the negative electrode active material particles can have good contact, and the negative electrode active material of the present application is applied to secondary batteries, which can increase the compaction density of the battery pole piece, thereby increasing the energy density of the secondary battery and improving the cycle performance of the secondary battery.
[0093] In some embodiments of the present application, in the negative electrode active material provided, the ratio of the ID / IG value of the first particle to the ID / IG value of the second particle is in the range of 0.93 to 1.12. Specifically, the ratio of the ID / IG value of the first particle to the ID / IG value of the second particle can be 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.10, 1.11, 1.12 or a range consisting of any two of the above values. In some embodiments of the present application, I D is the peak area of the D peak in the Raman spectrum of the negative electrode active material, I G It is the peak area of the G peak in the Raman spectrum of the negative electrode active material. The present application controls the ID / IG value of the first particle and the ID / IG value of the second particle of the provided negative electrode active material within the above range, so that the provided negative electrode active material has a suitable defect degree, which can promote ion adsorption and binding, and reduce the irreversible capacity loss caused by a high defect degree, thereby helping to improve the gram capacity of the negative electrode active material.
[0094] In some embodiments of the present application, in the negative electrode active material provided, the ID / IG of the first particle is in the range of 1.0 to 1.3. Specifically, the ID / IG of the first particle can be 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.3 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the range of ID / IG of the first particle within the above range, the provided negative electrode active material has a suitable degree of defects, which can promote ion adsorption and binding, while reducing the irreversible capacity loss caused by a high degree of defects, thereby helping to improve the gram capacity of the negative electrode active material.
[0095] In some embodiments of the present application, in the negative electrode active material provided, the ID / IG of the second particle is in the range of 1.1 to 1.3. Specifically, the ID / IG of the second particle can be 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.11, 1.12, 1.13, 1.14, 1.15, 1.16, 1.17, 1.18, 1.19, 1.20, 1.21, 1.22, 1.23, 1.24, 1.25, 1.26, 1.27, 1.28, 1.29, 1.3 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the range of ID / IG of the second particle within the above range, the provided negative electrode active material has a suitable degree of defects, which can promote ion adsorption and binding, while reducing the irreversible capacity loss caused by a high degree of defects, thereby helping to improve the gram capacity of the negative electrode active material.
[0096] In some embodiments of the present application, in the negative electrode active material provided, the strength of the first particle and the second particle is tested using nanoindentation, and the particle strength ratio of the first particle to the second particle ranges from 1.1 to 2.8. Specifically, the particle strength ratio of the first particle to the second particle can be 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8 or a range consisting of any two of the above values. In some embodiments of the present application, by regulating the particle strength ratio of the first particle and the second particle in the negative electrode active material provided by the present application within the above range, it can be ensured that the particle morphology of the negative electrode plate is maintained during the cold pressing process, thereby improving the first coulomb efficiency of the negative electrode active material and improving the cycle performance of the secondary battery.
[0097] In some embodiments of the present application, in the negative electrode active material provided, the strength of the first particle obtained by the nanoindentation method is in the range of 0.1 to 6 GPa. In some embodiments of the present application, by regulating the strength of the first particle obtained by the nanoindentation method within the above range, the particle morphology of the negative electrode sheet can be maintained during the cold pressing process to avoid crushing, thereby improving the first coulombic efficiency of the negative electrode active material and improving the cycle performance of the secondary battery.
[0098] In some embodiments of the present application, in the negative electrode active material provided, the strength of the second particle obtained by the nanoindentation method is in the range of 0.1 to 6 GPa. In some embodiments of the present application, by regulating the strength of the second particle obtained by the nanoindentation method within the above range, the particle morphology of the negative electrode sheet can be maintained during the cold pressing process to avoid crushing, thereby improving the first coulombic efficiency of the negative electrode active material and improving the cycle performance of the secondary battery.
[0099] According to the second aspect of the present application, the present application further provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising the negative electrode active material described in any one of the first aspects of the present application. The negative electrode plate provided in the second aspect of the present application has a high capacity, and applying it to a secondary battery can increase the energy density of the secondary battery while improving the cycle performance of the secondary battery.
[0100] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foamed nickel, foamed copper, or a polymer substrate coated with a conductive metal.
[0101] The negative electrode active material layer of the present application may also include a conductive agent and a binder. The present application has no particular restrictions on the above conductive agent and the above binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to carbon materials, metals or conductive polymers. The binder may include but is not limited to at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, hydroxypropyl cellulose, carboxymethyl cellulose (CMC) or sodium carboxymethyl cellulose (CMC-Na).
[0102] In some embodiments of the present application, the compaction density of the negative electrode active material layer is in the range of 0.90 to 1.3 g / cc; or, the compaction density of the negative electrode active material layer is in the range of 0.95 to 1.25 g / cc.
[0103] In some embodiments of the present application, the negative electrode plate is used as the working electrode and lithium metal is used as the counter electrode to assemble a half-cell, and a charge and discharge test is performed in the range of 0 to 2.5V vs Li+ / Li. In the charge and discharge curves obtained based on the charge and discharge test, the total gram capacity at 0 to 0.20V (vs Li+ / Li) is recorded as C10 mAh / g, and the gram capacity at 0 to 0.20V (vs Li+ / Li) is recorded as C11 mAh / g; the gram capacity at 0.2 to 2.5V (vs Li+ / Li) is recorded as C12 mAh / g, and the negative electrode active material satisfies 600≤C10≤850, 300≤C11≤590; and / or, 0.4≤C12 / C11≤1.2.
[0104] In some embodiments of the present application, in the negative electrode sheet provided, the compaction density of the negative electrode active material layer ranges from 0.90 to 1.3 g / cc. Specifically, the compaction density of the negative electrode active material layer can be 0.90 g / cc, 0.91 g / cc, 0.92 g / cc, 0.93 g / cc, 0.94 g / cc, 0.95 g / cc, 0.96 g / cc, 0.97 g / cc, 0.98 g / cc, 0.99 g / cc, 1.0 g / cc, 1.11 g / cc, 1.12 g / cc, 1.13 g / cc, 1.14 g / cc, 1 .15g / cc, 1.16g / cc, 1.17g / cc, 1.18g / cc, 1.19g / cc, 1.20g / cc, 1.21g / cc, 1.22g / cc, 1.23g / cc, 1.24g / cc, 1.25g / cc, 1.26g / cc, 1.27g / cc, 1.28g / cc, 1.29g / cc, 1.3g / cc or a range consisting of any two of the above values. Preferably, the compaction density range of the negative electrode active material layer can be 0.9 to 1.25g / cc. In some embodiments of the present application, by regulating the compaction density of the negative electrode active material layer within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0105] In some embodiments of the present application, in the provided negative electrode pole piece, the negative electrode pole piece is used as the working electrode and lithium metal is used as the counter electrode to assemble a half-cell, and a charge and discharge test is performed in the range of 0 to 2.5V vs Li+ / Li. In the charge and discharge curve obtained based on the charge and discharge test, the total gram capacity in the range of 0 to 0.20V (vs Li+ / Li) is recorded as C10mAh / g, and the gram capacity in the range of 0 to 0.20V (vs Li+ / Li) is recorded as C11 mAh / g; the gram capacity in the range of 0.2 to 2.5V (vs Li+ / Li) is recorded as C12 mAh / g, and the negative electrode active material satisfies 600≤C10≤850, 300≤C11≤590; and / or, 0.4≤C12 / C11≤1.2. Specifically, C10 can be 600mAh / g, 610mAh / g, 620mAh / g, 630mAh / g, 640mAh / g, 650mAh / g, 660mAh / g, 670mAh / g, 680mAh / g, 690mAh / g, 700mAh / g, 710mAh / g, 720mAh / g, 730mAh / g, 740mAh / g, 750mAh / g, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850 or a range consisting of any two of the above values. Specifically, C11 can be 300mAh / g, 310mAh / g, 320mAh / g, 330mAh / g, 340mAh / g, 350mAh / g, 360mAh / g, 370mAh / g, 380mAh / g, 390mAh / g, 400mAh / g, 410mAh / g, 420mAh / g, 430mAh / g, 440mAh / g, 450mAh / g, 460mAh / g, 470mAh / g, 480mAh / g, 490mAh / g, 500mAh / g, 510mAh / g, 520mAh / g, 530mAh / g, 540mAh / g, 550mAh / g, 560mAh / g, 570mAh / g, 580mAh / g, 590mAh / g, or a range consisting of any two of the above values. Specifically, C12 / C11 can be 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2 or a range consisting of any two of the above values. By adjusting the C10, C11, and C12 corresponding to the negative electrode active material within the above range, the negative electrode active material layer can have a high total lithium storage capacity and a low average lithium desorption potential. The negative electrode active material layer having the above characteristics is used as the negative electrode of a lithium ion battery, which is conducive to further improving the energy density of the lithium ion battery.
[0106] According to the third aspect of the present application, the present application provides a secondary battery, which includes the negative electrode sheet provided by any one embodiment of the second aspect of the present application. The secondary battery including the negative electrode sheet has high energy density and good cycle performance.
[0107] The secondary battery of the present application also includes a positive electrode sheet. The present application has no particular restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector. For example, the positive current collector may include a metal foil or a composite current collector, etc. For example, the metal foil is aluminum foil. In some embodiments, the secondary battery is a lithium-ion battery, and the positive electrode active material may include a lithium transition metal oxide, and the lithium transition metal oxide may include but is not limited to at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron manganese phosphate or lithium titanate.
[0108] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm.
[0109] The secondary battery of the present application also includes an electrolyte. In one embodiment, the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0110] The secondary battery of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm can include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex or aramid films, etc. At least one of the above.
[0111] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above-mentioned other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application. For example, an aluminum-plastic film packaging bag can be used.
[0112] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion battery, a sodium ion battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0113] According to a fourth aspect of the present application, the present application provides an electronic device, which includes the secondary battery provided by any one embodiment of the third aspect of the present application. The electronic device including the secondary battery has a long service life.
[0114] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0115] Example
[0116] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0117] The test methods used in the following examples and comparative examples are as follows:
[0118] 1. Particle sphericity test
[0119] Before the test, the particles in the negative electrode active material are screened. After the particles in the negative electrode active material are screened according to the particle size, the sphericity test of the corresponding particles is further performed. In the sphericity test of the particles, a laser particle size analyzer (model BT-2900) is used to analyze the sphericity of the solid powder based on the GB / T38887-2020 analysis method. Electromagnetic vibration sampling and free fall dispersion technology are used to disperse the solid powder, and the image processing software combined with high-speed CCD and multi-threading and edge recognition technology outputs the particle sphericity.
[0120] 2. Particle size test
[0121] The particle size of the powder material was tested using a Malvern particle size tester: the powder material was dispersed in an ethanol dispersant, and after ultrasonication for 30 minutes, the sample was added to the Malvern particle size tester to test the Dv50 of the powder material.
[0122] 3. Metal element analysis test
[0123] The sample was digested by a microwave digestion instrument (model CEM-Mars5), and the element content was quantitatively tested using an ICP-OES instrument (instrument model PE7000DV). After the sample was digested into a solution by acid, the liquid sample entered the atomization chamber, and formed an aerosol under the action of the carrier gas, and entered the plasma through the central injection tube to be fully evaporated, dissociated, atomized, ionized and excited, emitting the characteristic spectrum of the element, which was qualitatively determined based on the wavelength of the spectrum, and quantitatively analyzed based on the proportionality of the spectrum intensity to the concentration.
[0124] 4. Non-metallic element analysis test
[0125] X-ray photoelectron spectroscopy (instrument model: ThermoESCALAB250XI) was used to test the ratio and content of C and N elements in the active material. Three different parts of the same material were selected to test the content of the above elements and calculate their mass percentage.
[0126] 5. Scanning electron microscope (SEM) test of negative electrode active materials
[0127] A scanning electron microscope (ZEISSSEM) was used to observe the negative electrode active material particles and take SEM photos. For cross-section testing, an ion polisher (IB-09010CP) was used to cut out a flat cross section, followed by SEM photography. The principle of ion polishing is that under vacuum conditions, the ion source ionizes argon gas, and after acceleration and focusing, high-speed argon ions knock out atoms or molecules on the sample surface to achieve ion polishing.
[0128] 6. Small-angle X-ray scattering test
[0129] The sample was tested using a small angle X-ray scattering structure analyzer (instrument model: Nano-inXider) at a scattering intensity of 0.01nm -1 To 0.7nm -1 The scattering vector changes within a certain range are used to fit and analyze the closed pore volume in the negative electrode active material particles.
[0130] 7. Raman test
[0131] The Raman spectra of the first and second granular materials were tested by Raman spectrometer. A range of 200 μm × 500 μm was selected for testing, and more than 200 points were tested at equal intervals within the range. The test range of each point was 1000 cm -1Up to 2000cm -1 Between; recorded at 1320cm -1 Up to 1370cm -1 The peak between is the D peak, at 1570 cm -1 Up to 1620cm -1 The peak between the two points is the G peak, and the I D / I G The intensity ratio of the points is then calculated as the average value of the multiple points. D / I G Strength ratio.
[0132] 8. Particle strength test
[0133] The hardness and elastic modulus of a single particle of a porous material were tested using a nanoindenter (model: Hysitron TI 950), and the test standard was JB / T 12721-2016. Before the test, the powder was dispersed in epoxy resin and cured, and the cured resin was cut by ion polishing. A nanoprobe was used to pressurize a single particle, and the indentation depth on the particle surface was monitored to calculate the strength of the particle. The strength of five particles of the same sample was tested in parallel and the average value was taken.
[0134] 9. Compaction density test of negative electrode active material layer:
[0135] Take a fully discharged lithium-ion battery, disassemble the negative electrode sheet, clean it, dry it, use an electronic balance to weigh the negative electrode sheet with an area of S, record the weight as W1, and use a micrometer to measure the thickness T1 of the negative electrode sheet. Use solvent DMC to wash off the negative active material layer, dry it, measure the weight of the negative current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative current collector. Calculate the weight W0 and thickness T0 of the negative active material layer set on one side of the negative current collector and the compaction density of the negative active material layer by the following formula. W0 = W1-W2, T0 = T1-T2, then compaction density = W0 / (T0×S).
[0136] 10. Total gram capacity of lithium storage of negative electrode active materials and first efficiency test:
[0137] The first reversible gram capacity of the negative electrode active material from 0V to 2.5V can be obtained by the following test method: take a single-sided coated negative electrode sheet, cut it into a disc with a diameter of 14mm and use it as a working electrode, then use a lithium sheet as a counter electrode, and a porous polyethylene film (provided by Celgard) as a separator, inject electrolyte and assemble to obtain a button battery; first discharge the button battery to 0V with a three-stage small current of 0.05C / 0.01C / 0.005C, and record the first discharge capacity of the button battery; then charge it to 2.5V with a constant current of 0.1C, and record the first charging capacity of the button battery. First efficiency = first charge capacity / first discharge capacity × 100%; the first reversible gram capacity of the negative electrode active material in the Li / Li+ potential range of 0V to 2.5V, that is, the total gram capacity of lithium storage (total reversible capacity) C10 = first charge capacity / mass of negative electrode active material, in mAh / g; the first reversible gram capacity of the negative electrode active material in the Li / Li+ potential range of 0V to 0.2V + The gram capacity within the potential range is recorded as C11; the negative electrode active material is in the range of Li / Li + Li / Li in the potential range of 0.2V to 2.5V + The gram capacity within the potential range is recorded as C12.
[0138] The above-mentioned electrolyte includes a basic solvent and a lithium salt. The basic solvent is obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1. The lithium salt is LiPF6 and the concentration of the lithium salt is 1 mol / L.
[0139] The total gram capacity of lithium storage and the first efficiency test in the comparative example are the same as the total gram capacity of lithium storage and the first efficiency test methods of the above-mentioned negative electrode active materials.
[0140] 11. Energy density (ED) test
[0141] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 0.2C to a voltage of 4.48V or 3.95V, and then charged at a constant voltage; discharged at a constant current of 0.2C to a voltage of 2V, which is recorded as one cycle, and the discharge capacity C and discharge energy E of the first cycle are recorded; and the length, width and height of the battery at a 50% charge state are tested to obtain the volume V of the battery m Average discharge voltage U = E / C; energy density ED = E / V m .
[0142] Example 1-1
[0143] <Preparation of negative electrode active material>
[0144] (1) Prepolymerization: 1386 g of phenol and 1024 g of urotropine were weighed and dispersed in 32 L of aqueous solution. The mixed solution was placed in a 50 L glass reactor and stirred at room temperature for 2 h at a speed of 300 rpm. Then, the temperature was raised to the prepolymerization temperature of 95°C at a heating rate of 5°C / min, reacted for 24 h, and cooled to obtain a prepolymerized resin solution;
[0145] (2) Spray drying + curing: The prepared pre-polymerized resin solution is dried by spray drying, with the air inlet temperature controlled at 200°C, the air outlet temperature at 100°C, and the feed rate at 5L / min. After spraying, the powder product is collected; the powder product is placed in a programmable temperature-controlled oven under an inert atmosphere, and the temperature rise program is controlled to 90°C / 1h+110°C / 1h+130°C / 1h+150°C / 1h to ensure that the resin is fully cured to obtain a cured powder product;
[0146] (3) Carbonization: Weigh 1000 g of the solidified powder product and 100 g of LiOH, mix the two precursors evenly with a mixer, place the mixed precursor in a rotary kiln containing an inner tank, heat it to a primary calcination temperature T1 = 900 °C at a heating rate of 5 °C / min, carbonize for 2 h, cool it down, and obtain the carbonized material after cooling;
[0147] (4) Washing: The obtained carbonized powder material was washed with 1M hydrochloric acid for 12 h, filtered and the residue was washed with deionized water for 12 h, filtered and dried to obtain a dried powder;
[0148] (5) Carbon coating: The powder obtained after washing and drying is transferred into a nitrogen atmosphere protection furnace, and the temperature is increased to the vapor deposition temperature T3 = 900 °C at a heating rate of 5 °C / min. The gas atmosphere is then replaced with a mixture of reducing gases acetylene and argon. The vapor deposition time is t3 = 2h. After the vapor deposition is completed, the above-mentioned mixed gas is disconnected and replaced with nitrogen. After cooling to room temperature, a hard carbon material, i.e., a negative electrode active material, is obtained; wherein, based on the mass of the mixed gas, the mass percentage of the reducing gas acetylene is 20%.
[0149] <Preparation of negative electrode sheet>
[0150] The negative electrode active material prepared above was mixed with the binder styrene-butadiene rubber and the thickener sodium carboxymethyl cellulose in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 40wt%, and stirred evenly; the stirred negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and the copper foil was dried at 85°C for 4h to obtain a negative electrode sheet with a single-side coating of a negative electrode active material layer with a coating thickness of 50μm. After cold pressing, cutting and slitting, it was dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet with a specification of 76.6mm×875mm.
[0151] <Preparation of positive electrode sheet>
[0152] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder PVDF are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, stirred evenly, and a positive electrode slurry with a solid content of 72wt% is prepared. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material and a positive electrode active material layer thickness of 80μm. After cold pressing, cutting, and slitting, it is dried under vacuum conditions at 85°C for 4h to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0153] <Preparation of Electrolyte>
[0154] In a dry argon atmosphere glove box, the base solvents ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:PC:DEC=1:1:1, and then 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were added, dissolved and fully stirred, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte, wherein the concentration of the lithium salt was 1 mol / L, and based on the mass of the base solvent, the mass percentages of 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were all 2%.
[0155] <Preparation of Separator>
[0156] A polyethylene film with a thickness of 7 μm was used as the separator.
[0157] <Preparation of lithium-ion batteries>
[0158] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 80°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, shaping and other processes, a lithium-ion battery is obtained.
[0159] Examples 1-2 to 1-11 and Examples 2-1 to 2-8
[0160] Except for adjusting the preparation parameters according to Table a, the remaining preparation step parameters of Examples 1-2 to 1-11 and Examples 2-1 to 2-8 are the same as those of Example 1-1.
[0161] Comparative Example 1
[0162] Coconut shell is used to replace the precursor used in the step of <Preparation of negative electrode active material> of Example 1-1, that is, in step (3) of <Preparation of negative electrode active material> of Example 1-1, coconut shell is used as a precursor, that is, 1000g of coconut shell is directly weighed and placed in a rotary kiln containing an inner shell, and the temperature is increased to the primary calcination temperature T1=900°C at a heating rate of 5°C / min, carbonized for 2h, cooled, and the carbonized material is obtained after cooling, and the subsequent steps are continued. The remaining subsequent steps are the same as those of Example 1-1.
[0163] Comparative Example 2
[0164] Asphalt is used to replace the precursor used in the step <Preparation of negative electrode active materials> of Example 1-1, that is, in step (3) of <Preparation of negative electrode active materials> of Example 1-1, asphalt is used as a precursor, that is, 1000g of asphalt is directly weighed and placed in a rotary kiln containing an inner shell, and the temperature is increased at a heating rate of 5°C / min to a primary calcination temperature T1=900°C, carbonized for 2h, cooled, and the carbonized material is obtained after cooling, and the subsequent steps are continued. The remaining subsequent steps are the same as those of Example 1-1.
[0165] Table a
[0166]
[0167]
[0168] Effect Example 1
[0169] The first particle sphericity, first particle size, second particle sphericity, second particle size, first element type, mass percentage A1 of the first element in the first particle, mass percentage A2 of the first element in the second particle, second element type, mass percentage B1 of the second element in the first particle, mass percentage B2 of the second element in the second particle, A2 / A1, B2 / B1, compaction density of the negative electrode active material layer containing the above negative electrode active material, and related properties such as the total reversible capacity (mAh / g), energy density ED (Wh / L), and cycle retention rate (500 cycles) corresponding to the negative electrode active materials of each embodiment were further tested by the above test method. The results are shown in Table 1:
[0170] Table 1
[0171]
[0172]
[0173] From the results presented in Table 1, it can be seen that the negative electrode active material provided in the present application has a higher gram capacity and reversible capacity, and the lithium ion battery including the negative electrode active material of the present application has a higher energy density and a higher cycle retention rate, which indicates that the lithium ion battery provided in the present application has a higher energy density and better cycle performance. Combined with the data presented in the above examples, it can be seen that the negative electrode active material provided in the present application has a higher gram capacity and reversible capacity, and the lithium ion battery including the negative electrode active material of the present application has a higher energy density and a higher cycle retention rate, which indicates that the lithium ion battery provided in the present application has a higher energy density and better cycle performance.
[0174] At the same time, the scanning electron microscope photos of the negative electrode active materials of Examples 1-5 are as follows Figure 1 As shown, according to Figure 1The results shown show that the negative electrode active material is granular and contains two types of particles. The particles with smaller particle size have higher sphericity, and the particles with larger particle size have lower sphericity. In the negative electrode active materials corresponding to Examples 1-5, the sphericity of the first particle is 0.9, the sphericity of the second particle is 0.5, the particle size Dv50 of the first particle is 5μm, and the particle size Dv50 of the second particle is 12μm, that is, the sphericity of the first particle is higher than the sphericity of the second particle, and the particle size of the first particle is lower than the particle size of the second particle. The negative electrode active material with the above-mentioned particle morphology can be better combined with the first particle and the second particle, avoiding poor bonding performance due to point contact between the negative electrode active materials when there are only the first particles. At the same time, in the negative electrode active material provided by the present application, the first particles are evenly distributed between the second particles. The first particles with higher sphericity and smaller particle size can slide during the cold pressing process of the electrode piece, relieve cold pressing stress, avoid hard contact between particles, and thus avoid stress concentration. The problem of large particles being crushed by cold pressing is effectively solved, and more new surfaces of negative electrode materials are exposed after cold pressing, which further avoids electrolyte loss and improves the energy density and cycle performance of the battery. In addition, the compaction density of the negative electrode sheet containing the above-mentioned negative electrode active material is also significantly improved, and the negative electrode adhesive can better wrap the first particle, and the contact area between the cut surface of the first particle and the irregular surface of the second particle is larger, which can effectively promote the transmission of lithium ions between the negative electrode active materials.
[0175] Figure 2 The charge and discharge curves of a battery assembled with the negative electrode sheet prepared in Comparative Example 1 as the working electrode and the lithium metal sheet as the counter electrode in the potential range of 0V to 2.5V Li / Li+ are shown. Figure 2 It can be seen that in the Li / Li+ potential range of 0V to 0.2V, the specific capacity C11 of the negative electrode active material of Comparative Example 1 is 233mAh / g; in the Li / Li+ potential range of 0V to 2.5V, the specific capacity C10 of the negative electrode active material of Comparative Example 1 is 482mAh / g, and in the Li / Li+ potential range of 0.2V to 2.5V, the specific capacity C12 of the negative electrode active material of Comparative Example 1 is 249mAh / g.
[0176] Figure 3 The charge and discharge curves of the battery assembled with the negative electrode sheet prepared in Example 1-5 as the working electrode and the lithium metal sheet as the counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown; Figure 3It can be seen that within the Li / Li+ potential range of 0V to 0.2V, the specific capacity C11 of the negative electrode active material of Examples 1-5 is 582mAh / g; within the Li / Li+ potential range of 0V to 2.5V, the specific capacity C10 of the negative electrode active material of Examples 1-5 is 820mAh / g, and within the Li / Li+ potential range of 0.2V to 2.5V, the specific capacity C12 of the negative electrode active material of Examples 1-5 is 238mAh / g. Compared with Comparative Example 1, the negative electrode active material provided in the examples of the present application has a significantly higher specific capacity, and the negative electrode active material of Examples 1-5 has a stable low potential platform, and exhibits a higher energy density when applied to a full battery.
[0177] Effect Example 2
[0178] Based on the results presented in Table 1, the coating thickness of the negative electrode active materials prepared in Examples 2-1 to 2-8, the mass ratio of the first particle to the second particle, the closed pore volume cc / g of the first particle, the closed pore volume cc / g of the second particle, the first particle ID / IG, the second particle ID / IG, the strength ratio of the first particle to the second particle, the first particle strength (Gpa) and other parameters, as well as the total reversible capacity (mAh / g), energy density ED (Wh / L), cycle retention rate (500 cycles) and other related properties of the negative electrode active materials of each embodiment were further tested by the above-mentioned test method. Each embodiment (Example 2-1 to Example 2-8) in Table 2 is based on Example 1-2, keeping the corresponding product parameters in Table 1 basically the same as Example 1-2, only changing the corresponding product parameters in Table 2, and comparing the changes in the relevant properties corresponding to each embodiment in Table 2. The results are shown in Table 2:
[0179] Table 2
[0180]
[0181] The results presented in Table 2 further indicate that the negative electrode active material provided in the present application has higher gram capacity and reversible capacity. The lithium ion battery including the negative electrode active material of the present application has higher energy density and higher cycle retention rate. When the coating thickness of the negative electrode active material, the mass ratio of the first particle to the second particle, the closed pore volume cc / g of the first particle, the closed pore volume cc / g of the second particle, the first particle ID / IG, the second particle ID / IG, the intensity ratio of the first particle to the second particle, the first particle strength and other parameters are further adjusted based on the product parameters in Table 1, the total reversible capacity (mAh / g), energy density ED (Wh / L), cycle retention rate (500 cycles) and other properties of the negative electrode active material can be further improved.
[0182] at the same time, Figure 4The charge and discharge curves of the battery assembled with the negative electrode sheet prepared in Example 2-4 as the working electrode and the lithium metal sheet as the counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown. Figure 4 It can be seen that within the Li / Li+ potential range of 0V to 0.2V, the specific capacity C11 of the negative electrode active material of Examples 2-4 is 334mAh / g; within the Li / Li+ potential range of 0V to 2.5V, the specific capacity C10 of the negative electrode active material of Examples 2-4 is 641mAh / g, and within the Li / Li+ potential range of 0.2V to 2.5V, the specific capacity C12 of the negative electrode active material of Examples 2-4 is 307mAh / g. Compared with Comparative Example 1, the negative electrode active material provided in the examples of the present application has a higher specific capacity, and the negative electrode active material of Examples 2-4 has a stable low potential platform, and exhibits a certain energy density when applied to a full battery.
[0183] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present invention are within the scope of protection of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material is in a granular form and includes a first particle and a second particle. The sphericity of the first particle is greater than that of the second particle, the sphericity of the first particle is 0.6 to 1.0, and the particle size Dv50 of the first particle is smaller than that of the second particle.
2. The negative electrode active material according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions (1) to (5): (1) The sphericity of the first particles is 0.7 to 1.0; (2) The sphericity of the second particles is 0.1 to 0.6; or, the sphericity of the second particles is 0.2 to 0.6; (3) The ratio of the sphericity of the first particles to the second particles is in the range of 1.1 to 10.0; or the ratio of the sphericity of the first particles to the second particles is in the range of 1.1 to 5.5; (4) The first particles include hard carbon material; (5) The second particles include a hard carbon material.
3. The negative electrode active material according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions (6) to (8): (6) The particle size Dv50 of the first particles is in the range of 1 μm ≤ Dv50 ≤ 10 μm; or, the particle size of the first particles is The Dv50 range is 3μm≤Dv50≤8μm; (7) The particle size range of the second particles is 1.5 μm ≤ Dv50 ≤ 20 μm; or the particle size Dv50 range of the first particles is 8 μm ≤ Dv50 ≤ 20 μm; (8) The ratio of the particle size Dv50 of the first particles to the particle size Dv50 of the second particles is in the range of 0.05 to 0.9; or the ratio of the particle size Dv50 of the first particles to the particle size Dv50 of the second particles is in the range of 0.1 to 0.
9.
4. The negative electrode active material according to claim 1, characterized in that The first particles and the second particles further contain a first element and a second element, wherein the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; and the second element is N.
5. The negative electrode active material according to claim 4, characterized in that The negative electrode active material satisfies at least one of the following conditions (9) to (12): (9) Based on the total mass of the negative electrode active material, the content of the first element relative to the total mass of the negative electrode active material is 0.01% to 1%; (10) Based on the total mass of the first particle, the content of the first element in the first particle is A1, based on the total mass of the second particle, the content of the first element in the second particle is A2, and A2 / A1 satisfies the following relationship: 0.8≤A2 / A1≤1.2; and / or, the content A1 of the first element in the first particle is in the range of 0.01% to 0.9%; and / or, the content A2 of the first element in the second particle is in the range of 0.01% to 0.9%; (11) Based on the total mass of the negative electrode active material, the content of the second element relative to the total mass of the negative electrode active material is 0.01% to 3%; (12) Taking the total mass of the first particle as a reference, the content of the second element in the first particle is B1, and the content of the second element in the second particle is B2, and B2 / B1 satisfies the following relationship: 0.8≤B2 / B1≤1.2; and / or, the content B1 of the second element in the first particle is in the range of 0.06% to 2.8%; and / or, the content B2 of the second element in the second particle is in the range of 0.05% to 3%.
6. The active substance according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions (13) to (15): (13) The ratio of the closed pore volume of the first particles to that of the second particles is 0.75 to 1.0; (14) The closed pore volume of the first particles is in the range of 0.05 to 0.4 cc / g; or, the closed pore volume of the first particles is in the range of 0.12 to 0.36 cc / g; (15) The closed pore volume of the second particles is in the range of 0.06 to 0.4 cc / g; or, the closed pore volume of the second particles is in the range of 0.06 to 0.34 cc / g.
7. The negative electrode active material according to claim 1, characterized in that The negative electrode active material satisfies at least one of the following conditions (16) to (19): (16) The first particle and the second particle also have a carbon coating layer on their surfaces respectively; the thickness of the carbon coating layer is 20 to 200 nm; (17) The particle mass ratio of the first particles to the second particles is 0.6 to 3.0; (18) The ratio of the ID / IG value of the first particle to the ID / IG value of the second particle is in the range of 0.93 to 1.12; and / or, the ID / IG value of the first particle is in the range of 1.0 to 1.3; and / or, the ID / IG value of the second particle is in the range of 1.0 to 1.3; (19) The strength of the first particle and the second particle is tested by a nanoindentation method, and the ratio of the strength of the first particle to the second particle is in the range of 1.1 to 2.8; or, the strength of the first particle is in the range of 0.1 to 6.0 GPa; or, the strength of the second particle is in the range of 0.1 to 6.0 GPa.
8. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode active material according to any one of claims 1 to 7.
9. The secondary battery according to claim 8, characterized in that: The negative electrode sheet satisfies at least one of the following conditions (20) to (21): (20) The compaction density of the negative electrode active material layer is in the range of 0.90 to 1.3 g / cc; or, the compaction density of the negative electrode active material layer is in the range of 0.9 to 1.25 g / cc; (21) The negative electrode sheet is used as the working electrode and lithium metal is used as the counter electrode to assemble a half-cell. + / Li range, and the charge-discharge curve obtained based on the charge-discharge test is between 0 and 0.20V (vs Li + / Li) is recorded as C10 mAh / g, and the total gram capacity is recorded as C10 mAh / g at 0 to 0.20V (vs Li + / Li) is recorded as C11mAh / g, at 0.2 to 2.5V (vs Li + The gram capacity of the negative electrode (A / Li) is recorded as C12 mAh / g, and the negative electrode active material satisfies: 600≤C10≤850, 300≤C11≤590; and / or, 0.4≤C12 / C11≤1.
2.
10. An electronic device, characterized in that: The electronic device comprises the secondary battery as claimed in any one of claims 8 or 9.
Citation Information
Patent Citations
Negative electrode material, and electrochemical device and electronic device including same
CN111146414A
Negative active material, negative pole piece, secondary battery, battery module, battery pack and electric device thereof
CN115832232A
Secondary battery and electronic device
CN116487527A
Negative pole piece, secondary battery and device
CN118538867A
Material for negative electrode of non-aqueous electrolyte secondary battery, process for producing the same, negative electrode and battery
US20090140214A1